Parametric study of biomass oil (palm kernel shell oil) based bio adhesive formulation: article / Nur ‘Aliah Arish and Azil Bahari Alias - Arish, Nur ‘Aliah; Alias, Azil Bahari (2017)
Adhesives are used widely in the wood, metal, paper, leather, rubber and glass industries, the demand for these liquid natural adhesives gradually increased. Biomass is a lignocellulosic material which consists of components such as cellulose, hemi-cellulose and lignin. In commercial wood adhesive, phenol formaldehyde act as the raw material, but this substance is not environmentally friendly, cause pollutant and is harmful to human health. This study will compare the physical and chemical properties of the bio based phenolic resins derived from the palm kernel shell with the reference phenol formaldehyde. Formulating the produced palm kernel shell oil, bio based adhesive on a different set of parameters (temperature, time and catalyst loading) with comparison study to the reference phenol formaldehyde adhesive. The objective of the study is to characterize the physical and chemical properties of bio based phenolic resin from palm kernel shell oil and formulate a bio based adhesive on different set of conditions (temperature, time and catalyst loading. Method of formulation need to be improved in terms of increasing or keeping the amount of phenol required. As far as being studied in this paper, it is by manipulating the set of parameter through resinification reaction of bio based oil.